Influence of the extent of cervical lymph node dissection and lymph nodes metastases on prognosis in a cohort of dogs with oral malignant melanoma treated by surgical resection and adjuvant anti-CSPG4 electrovaccination: a retrospective study on 77 cases - Giacobino, Davide; Olimpo, Matteo; Ferraris, Erica Ilaria; Martinelli, Greta; Maniscalco, Lorella; Camerino, Mariateresa; Riccardo, Federica; Cavallo, Federica; Tarone, Lidia; Cino, Marzia; Dentini, Alfredo; Iussich, Selina; et al. (Frontiers in Veterinary Science, 2025)
The most appropriate approach to regional/sentinel lymph nodes (LN) for staging canine oral malignant melanoma (OMM) is still controversial. This study aims to retrospectively evaluate the prognostic impact of neck dissection modality and LN metastasis in a homogeneous cohort of dogs treated by surgery and adjuvant anti-CSPG4 electrovaccination. Seventy-seven dogs were enrolled and divided into two groups based on the presence (Group A, 24 dogs) or absence (Group B, 53 dogs) of histologically confirmed LN metastasis at the time of surgery. The overall LN metastatic rate was 31%; metastasis was found mostly in the mandibular lymph center (83%). Median survival time (MST) and disease-free interval (DFI) in Group A were 406 and 134 days, respectively. Although shorter, these values were not significantly different from MST and DFI in Group B (534 and 219 days, respectively; p = 0.16 and p = 0.11). Stratifying the cases based on the type of lymphadenectomy performed, no statistical differences were observed between Groups 1 (ipsilateral lymphadenectomy) and 2 (bilateral lymphadenectomy) regarding both MST and DFI. Similarly, no significant differences in MST and DFI were observed among subgroups based on ipsilateral (Group 4) and bilateral (Group 6) removal versus ipsilateral (Group 3) and bilateral (Group 5) non-removal of even the medial retropharyngeal LN. No association was found between LN metastasis and recurrence or distant metastasis. Finally, no association was found between lymphadenectomy pattern and progressive disease. The results recorded in this study, i.e., that ipsilateral mandibular lymphadenectomy may be a reasonable surgical option in OMM, apply for this cohort of dogs only, and the translation of this principle to canine OMMs differently treated needs further investigations. Additionally, further efforts should be addressed to studies on sentinel LN identification for canine OMM staging.